Skeletal muscle signature of a champion sprint runner - Trappe, S.; Luden, N.; Minchev, K.; Raue, U.; Jemiolo, B.; Trappe, T. A. (Journal of Applied Physiology, 2015)
We had the unique opportunity to study the skeletal muscle characteristics, at the single fiber level, of a world champion sprint runner who is the current indoor world record holder in the 60-m hurdles (7.30 s) and former world record holder in 110-m hurdles (12.91 s). Muscle biopsies were obtained from the vastus lateralis at rest and 4 h after a high-intensity exercise challenge (4 × 7 repetitions of resistance exercise). Single muscle fiber analyses were conducted for fiber type distribution (myosin heavy chain, MHC), fiber size, contractile function (strength, speed, and power) and mRNA expression (before and after the exercise bout). The world-class sprinter's leg muscle had a high abundance (24%) of the pure MHC IIx muscle fibers with a total fast-twitch fiber population of 71%. Power output of the MHC IIx fibers (35.1 ± 1.4 W/l) was 2-fold higher than MHC IIa fibers (17.1 ± 0.5 W/l) and 14-fold greater than MHC I fibers (2.5 ± 0.1 W/l). Additionally, the MHC IIx fibers were highly responsive to intense exercise at the transcriptional level for genes involved with muscle growth and remodeling (Fn14 and myostatin). To our knowledge, the abundance of pure MHC IIx muscle fibers is the highest observed in an elite sprinter. Further, the power output of the MHC IIa and MHC IIx muscle fibers was greater than any human values reported to date. These data provide a myocellular basis for the high level of sprinting success achieved by this individual.